Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.jad.2020.06.047
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression and its impact on quality of life among frontline nurses in emergency departments during the COVID-19 outbreak

Abstract: Highlights ED nurses exposed to COVID-19 could be psychologically and mentally exhausted. Prevalence of depression among 1,103 ED nurses was 43.61% (95% CI=40.68%–46.54%). A heightened awareness of and timely treatment for depression for frontline ED nurses should be provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
242
2
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(271 citation statements)
references
References 24 publications
(28 reference statements)
16
242
2
11
Order By: Relevance
“… Country or region Design Epidemic studied Participants Duration and year Measures An et al. (2020) ( An et al., 2020 ) China Cross-sectional COVID-19 1,103 nurses 6 days, March 2020 PHQ-9 and WHO-QOL-BREF Babore et al. (2020) ( Babore et al., 2020 ) Italy Cross-sectional COVID-19 595 health care workers 6 days, April 2020 PSS and COPE-NVI-25 Bai et al.…”
Section: Resultsmentioning
confidence: 99%
“… Country or region Design Epidemic studied Participants Duration and year Measures An et al. (2020) ( An et al., 2020 ) China Cross-sectional COVID-19 1,103 nurses 6 days, March 2020 PHQ-9 and WHO-QOL-BREF Babore et al. (2020) ( Babore et al., 2020 ) Italy Cross-sectional COVID-19 595 health care workers 6 days, April 2020 PSS and COPE-NVI-25 Bai et al.…”
Section: Resultsmentioning
confidence: 99%
“…The main occupational factors were working in a high-risk environment, higher perception of threat and risk, specialised training received, and specific occupational role. Working in a high risk environment was associated with different mental health problems, namely depression ( Lai et al 2020 , An et al 2020 , Chatterjee et al 2020 , Elbay et al 2020 , Lu et al 2020 , Ni et al 2020 , Huajun Wang et al 2020, Wu et al 2008 ), anxiety ( Lai et al 2020 , Li et al 2015 , Matsuishi et al 2012 , Verma et al 2004 , Dosil Santamaria et al 2020 , Elbay et al 2020 , Liu et al 2020 , Lu et al 2020 , Ni et al 2020 , Que et al 2020 , Huajun Wang et al 2020, Zhang et al 2020 ), PTSD ( Bukhari et al 2016 , Styra et al 2008 , Tang et al 2017 , Wu et al 2009 , Wu et al 2008 , Arpacioglu et al 2020 ), and burnout ( Tolomiczenko et al 2005 ). The definition of high risk environment varied across studies, but usually included being in direct contact with infected patients, either providing care ( Bukhari et al 2016 , Verma et al 2004 ) or being responsible for cleaning and disinfection ( Li et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…In our survey, 86.57% of HCWs in Wuhan, 89.37% of HCWs in other cities in Hubei except Wuhan, and 71.22% of HCWs in other provinces in China except Hubei were worried about their family's cross-infection because of them. Given the high infectivity of the virus and its transmission through respiratory droplets and close contact, fear of inadvertently endangering members of family and loved ones was a widespread concern among HCWs (8). The HCWs were torn between their own responsibilities and this concern.…”
Section: Discussionmentioning
confidence: 99%
“…As of February 17, 2020, Chinese officials reported that more than 3,000 HCWs had been infected with COVID-19. Another important reason for the psychological burden on HCWs is the greater fear of their family members being at a higher risk of infection (8)(9)(10)(11). Therefore, when new epidemics break out, HCWs often suffer from huge psychological health problem, such as anxiety and depression (12,13).…”
Section: Introductionmentioning
confidence: 99%